Predictive Factors of Response to Neoadjuvant Chemotherapy (NACT) and Immune Checkpoint Inhibitors in Early-Stage Triple-Negative Breast Cancer Patients (TNBC) - Khashayar Yazdanpanah Ardakani; Francesca Fulvia Pepe; Serena Capici; Thoma Dario Clementi; Marina Elena Cazzaniga (Current Oncology, 2025)
Triple-negative breast cancer (TNBC) is a heterogenous group of breast tumors. This type of breast tumor is relatively difficult to manage, due to the lack of expression of Hormone Receptors (HR) and human epidermal growth factor receptor (HER2). Efforts have been made to understand the factors involved in determining how a triple-negative breast tumor responds to therapy. The standard of treatment in most cases today is a combined modality of immune checkpoint inhibitors (ICIs) and chemotherapy with agents such as anti-mitotic (taxanes) or DNA-damaging agents (alkylating agents, cyclophosphamides, platin salts). In this study, we investigated the predictive and prognostic factors for TNBC, in the neoadjuvant setting; understanding each patient’s response before treatment initiation is crucial to guiding the subsequent approach and finally improving patient outcomes. We focused on tumor-infiltrating lymphocytes at the site of the primary tumor (TILs), circulating tumor cells (CTCs), circulating tumor DNA (ctDNA), the mutational status of protein 53 (p53), and Ki-67, investigating the potential roles of these factors in predicting responses to anti-cancer agents.